Investigating Life Satisfaction and Resiliency Levels of High School Students based on the Relation with Parental Attitudes - Ciftci Aridag, Nermin; Unsal Seydoogullari, Sedef (HACETTEPE UNIV, 2019)
The purpose of this study is to examine life satisfaction and resilience levels of high school students with respect to parental attitudes. In addition, whether or not the life satisfaction and resilience levels of students differ with respect to gender and perceived academic achievement was aimed at being examined. Also whether or not parental attitude and life satisfaction predicts resilience significantly. The study group consists of 679 students studying in various high schools in Istanbul and Kocaeli. The Personal Information Form, Satisfaction with Life Scale, Resiliency Scale and Parental Attitude Scale were used in collecting the data. According to the study findings; relationships were observed between life satisfaction and resilience and with parental attitudes. Positive, weak and significant relationships were detected between democratic parental attitude and life satisfaction and resilience. Weak and negative significant relationships were observed between authoritarian mother and authoritarian father with life satisfaction and resilience. According to our findings, it was observed that life satisfaction and resilience levels do not differ based on gender. Life satisfaction levels of students who perceive their academic achievement low were observed to be lowers than life satisfaction levels of students who perceive their academic achievement good and very good. Resilience levels of students who perceive their academic achievement low were again observed to be lower than resilience levels of students who perceive their academic achievement below medium, medium, good and very good. Also levels of students who perceive their academic achievement medium again observed to be lower than resilience levels of students who perceive their academic achievement good. Parental attitude and life satisfaction predict resilience at a significant level. Findings were discussed by relating the results with the studies in the literature.
Keywords: High school students; life satisfaction; resilience; parental attitude; academic success; UNIVERSITY-STUDENTS; SOCIAL SUPPORT; SELF-CONCEPT; ADOLESCENTS; PERSONALITY; ADJUSTMENT; VALIDATION; PREDICTORS; BEHAVIOR; Education & Educational Research